Kunskap om barnkonventionen : En studie om lärares upplevelse av barnkonventionen i skolan - Krane, Linn (2012)
The purpose of this study is to find a plausible explanation to why knowledge of the convention of the rights of the child is lacking among the pupils in Luleå municipality as is proved by the Save the Children survey of 2011. Teachers in Luleå municipality, from primary to secondary school, were interviewed in order to get a perspective of their experience of information concerning the convention and the way they look upon it. The reason for interviewing teachers was because they work with pupils on a daily basis, in and outside the classroom. The study showed that the teachers experience receiving little information about the convention of the rights of the child during education and work. The principles of the convention is, however, very fundamental in the schools and in the work of the teachers. The convention is thereby largely implemented in these schools. The conclusion that the schools would benefit from further information to teachers and pupils was drawn after an analysis of the empirical material in relation to relevant theories. Keywords: the convention of the rights of the child, knowledge and information Validerat; 20120923 (anonymous)